A Simplified Method of Calculating Propeller Parameters for Small Trawlers - Husin, Juhari; Shahardin, Zainal Ashirin (1984)
It is quite common to encounter a propeller installed on a trawl that does not develop adaquate thrust to pull the trawl at a specified trawling speed. The immediate actions usually taken are to reduce the size of a trawl, change to a new propeller or install a higher powered engine. All these alternatives will impose a financial strain on the fishermen. Therefore, a simple method of calculation is being suggested to obtain a spectrum of propeller parameters such as diameter, pitch- diameter ratio, speed, quasipropulsive coefficient and propeller performance coefficient for a given engine model. The best combination of parameters can be obtained in order to satisfy a specific trawling requirement. Usually the requirement is stated in the form of thrust of propeller to overcome total gear drag at a specific trawling speed. Total gear drag can be determined by a model test or mathematical modelling. Three engine models have been studied and for each model values of thrusts, propeller performance coefficients and quasi- propulsive coefficient were calculated. Having known the values of torque coefficient (J.l) and advance coefficient (¢) the values of pitch- diameter ratios were obtained from propeller performance curve.